X chromosome in aged hematopoietic stem cells (HSC) - Florian, Maria Carolina (Dryad, 2020)
During X chromosome inactivation (XCI), the inactive X chromosome (Xi) is
recruited to the nuclear lamina at the periphery of the nucleus. Beside X
chromosome reactivation resulting in a highly penetrant aging-like
hematopoietic malignancy, little is known about XCI in aged hematopoietic
stem cells (HSCs) . Here, we demonstrate that LaminA/C defines a distinct
repressive nuclear compartment for XCI in young HSCs, and its reduction in
aged HSCs correlates with an impairment in the overall control of XCI.
Integrated omics analyses reveal higher variation in gene expression,
global hypomethylation and significantly increased chromatin accessibility
on the X chromosome in aged HSCs. In summary, our data support the role of
LaminA/C in the establishment of a special repressive compartment for XCI
in HSCs, which is impaired upon aging.
Refer to the original manuscript for details about methods for each dataset.
This dataset contains data related to the manuscript “Attrition of X
chromosome inactivation in aged hematopoietic stem cells by” Grigoryan A.
et al, Stem Cell Reports, 2021. It contains 4 tables with sequencing data
results related to the associated manuscript: Table S1. Related to Figure
1. Chr X allele-specific expression (ASE) data for each given cells.
p-value indicates allele-specific expression significance. A summary of
the data with statistical analysis is shown at the end of the ASE
expression dataset. Table S2. Related to Figure 2. List of the 5835 Chr
X-based differentially methylated regions (DMRs) at a q-cutoff value of
0.05. The 113 DMRs with a mean difference greater than or equal to 0.1
with at least 3 methylation marks representing them are listed at the
bottom. Table S3. Related to Figure 2. ATAC-seq peaks identified along
ChrX in young and aged HSCs. Table S4. Related to Figure 2. Differential
accessible regions (DARs) (p.value < 0.05) comparing young vs aged
HSCs. List of the 1302 (genome-wide; upper part) and 64 (Chr X-specific;
bottom) statistically significant DARs. Moreover, it includes and
additional excel file, which lists all raw data used to generate the
graphs depicted in Figure 1 and Figure 2 of the associated manuscript. In
panel 1C, it is reported the mean percentage of young HSCs with
localization of Xist close to the tubulin pole. In panel 1E, it is
listed the measurements (µm) of the distances between Chr X/Y and
tubulin, Chr X/X and tubulin in young male and female HSCs. In panel 1G,
it is reported the mean percentage of young HSCs with a polar distribution
of Pol II Ser2ph. In panels I and J, it is listed Xist distance (µm) from
the edge of the nucleus and Xist volume (µm3) measurements. In panel
related to Figure 2 A and B, data are Xist relative transcript levels in
young and aged female HSCs and ST-HSCs (respectively in this order)
measured by RT-PCR. From left to right it is shown the relative
expression level, SD and n for each sample set.